HUBUNGAN PENGETAHUAN, SIKAP, SARANA DAN JENIS KELAMIN DENGAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI ASRAMA RIAU, YOGYAKARTA - Dyah Suryani; Ozy Syahputra (Universitas Ahmad Dahlan, 2021)
Clean and healthy living behavior is behavior based on the desire, willingness, and ability of people to help themselves in the health sector and to be able to play an active role in health activities. In terms of equitable development with a health perspective, it includes all groups of society, both groups of children and groups of adults: the factor that can influence and attitudes. There are still residents in the Riau Yogyakarta Student Dormitory who do not know how to live clean and healthy, and the prerequisites support a clean and healthy lifestyle. The purpose of this study was to analyze the relationship between knowledge, attitudes, facilities, and gender for clean and healthy living behavior (CHLB) in Riau Yogyakarta Dormitory. This study used a cross-sectional study. The population of this study was residents of the Riau Yogyakarta student dormitory. The sampling technique was carried out by total sampling (41 respondents). The research instrument was a questionnaire of knowledge, attitudes, facilities, sex, and CHLB. Data analysis using univariate analysis and bivariate analysis using Chi-square test. The results of the bivariate analysis showed that there was a relationship between knowledge and CHLB of dormitory residents p= 0,002, there was a relationship between attitudes and CHLB of dormitory residents p= 0,000, there was a relationship between facilities and CHLB of dormitory residents p= 0,000, and there was a relationship between sex and CHLB dorm residents p= 0,005. There is a relationship between knowledge, attitudes, facilities, and gender with CHLB dormitory residents in Riau Yogyakarta.